Evaluation of Modified Essay Questions (MEQ) and Multiple Choice Questions (MCQ) as a tool for Assessing the Cognitive Skills of Undergraduate Medical Students - Khan, Moeen-uz-Zafar; Aljarallah, Badr Muhammad (International Journal of Health Sciences, 2011)
Objectives: Developing and testing the cognitive skills and abstract thinking of undergraduate medical students are the main objectives of problem based learning. Modified Essay Questions (MEQ) and Multiple Choice Questions (MCQ) may both be designed to test these skills. The objectives of this study were to assess the effectiveness of both forms of questions in testing the different levels of the cognitive skills of undergraduate medical students and to detect any item writing flaws in the questions. Methods: A total of 50 MEQs and 50 MCQs were evaluated. These questions were chosen randomly from various examinations given to different batches of undergraduate medical students taking course MED 411-412 at the Department of Medicine, Qassim University from the years 2005 to 2009. The effectiveness of the questions was determined by two assessors and was defined by the question’s ability to measure higher cognitive skills, as determined by modified Bloom’s taxonomy, and its quality as determined by the presence of item writing flaws. ’SPSS15’ and ’Medcalc’ programs were used to tabulate and analyze the data. Results: The percentage of questions testing the level III (problem solving) cognitive skills of the students was 40% for MEQs and 60% for the MCQs; the remaining questions merely assessed the recall and comprehension. No significant difference was found between MEQ and MCQ in relation to the type of questions (recall; comprehension or problem solving x2 = 5.3, p = 0.07).The agreement between the two assessors was quite high in case of MCQ (kappa=0.609; SE 0.093; 95%CI 0.426 â€“ 0.792) but lower in case of MEQ (kappa=0.195; SE 0.073; 95%CI 0.052 â€“ 0.338). 16% of the MEQs and 12% of the MCQs had item writing flaws. Conclusion: A well constructed MCQ is superior to MEQ in testing the higher cognitive skills of undergraduate medical students in a problem based learning setup. Constructing an MEQ for assessing the cognitive skills of a student is not a simple task and is more frequently associated with item writing flaws.